Directive Function in a Tourism Discourse: A Corpus-Based Analysis - Suhaimi; Taufik Afdal (Universitas Airlangga, 2023)
The promotion of tourism through guidebooks stands as a pivotal marketing strategy to entice visitors to their desired destinations. However, a considerable number of tourism books fall short due to inadequacies in adhering to the language of tourism (LoT) criteria. Among the essential functions within tourism discourse is the directive function, with a specific focus on imperative verbs. This study employs a corpus-based approach to identify and classify imperative verbs in the Three Sixty Guide Bali, according to their functions in the guidebook. The imperative verbs are categorized for various purposes, including food attractions, health services, sports activities, retreats, zoo visits, shows, and party recommendations. The analysis reveals approximately 94 verbs serving directive functions in the guidebook, imbued with persuasive nuances aimed at captivating readers and transforming them into potential customers. These findings offer valuable insights for tourism guidebook writers and website developers, facilitating the creation of persuasive and compelling guides that assure prospective tourists of the services, amenities, and experiences awaiting them.